PENGARUH LAMA PERENDAMAN DENGAN MENGGUNAKAN LARUTAN DAUN SALAM (Syzygium polyanthum) SEBAGAI PENGAWET TERHADAP TOTAL BAKTERI Coliform DAN E.coli DAGING BROILER - Triwidayanti, Okti; Santosa, Purnama Edy; Septinova, Dian (JURUSAN PETERNAKAN, FAKULTAS PERTANIAN, UNIVERSITAS LAMPUNG, 2017)
This research was conducted in May - June 2017 at Animal Production and Reproduction Laboratory, Animal Husbandry Departement, Faculty of Agriculture, University of Lampung and Veterinary Public Health Laboratory of Lampung. This research intended to determine the effect of immersion duration in salam leaf on total content of Coliform and E. coli bacteria of broiler meat. The research was conducted using 4 immersion treatments that is P0 (broilers without immersion), P1 (broilers soaked for 20 minutes), P2 (broilers soaked for 40 minutes) and P3 (broilers meat soaked for 60 minutes). In this research there is 5 replications in each treatment, so there is 20 experimental units and each experimental unit used 1 broiler chicken breast. The material used in this research is 20 units of 1month old Lohman male broiler chickens with 1 kg of body weight. The data obtained in this research is made in tabulation and analyzed descriptively. The results of this research indicated that broiler immersion duration in salam leaf solution did not decrease the total content of Coliform and E.coli bacteria. Key words: broiler meat, immersion duration, salam leaf, Coliform, and E. coli.